2008
DOI: 10.1024/0301-1526.37.1.61
|View full text |Cite
|
Sign up to set email alerts
|

L-arginine plasma levels and severity of idiopathic pulmonary arterial hypertension

Abstract: The results suggest a possible role of the NO precursor L-arginine in the pathogenesis of iPAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The bioavailability of L-arginine to NOS has been shown to affect NO production [29]. For example, infants with persistent pulmonary hypertension of the newborn had lower plasma levels of L-arginine and lower plasma nitrates than did infants without pulmonary hypertension [2,25]. The mechanism of PH in the newborn, however, may be different than that of PH associated with congenital heart disease and this will also need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The bioavailability of L-arginine to NOS has been shown to affect NO production [29]. For example, infants with persistent pulmonary hypertension of the newborn had lower plasma levels of L-arginine and lower plasma nitrates than did infants without pulmonary hypertension [2,25]. The mechanism of PH in the newborn, however, may be different than that of PH associated with congenital heart disease and this will also need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…96 This leads to a depletion of L-arginine, which has been shown to be strongly correlated with right atrial pressure, cardiac index, and 6-min walk distance in patients with idiopathic PAH. 97 It is important to note that although increased arginase is associated with decreased NO production, arginase may also contribute to the vasculopathy of PAH through NO-independent pathways, especially via increased polyamine synthesis and the subsequent stimulation of vascular proliferation and remodelling. 14…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%
“…Still, in our study, there was a significant difference in l -arginine between PAH and LVSD and this is an important finding. Furthermore, Beyer et al showed a strong correlation between plasma l -arginine levels and severity of idiopathic PAH [ 32 ]. Currently, there are no known biomarkers to separate PAH to LVSD.…”
Section: Discussionmentioning
confidence: 99%